Framing Analysis of High-speed Rail Project Reports on Online Media Kompas.com, and Viva.co.id - M. Fatich Ilham Z; Lukman Hakim (Lingkar Studi Komunikasi (LISKI), 2023)
This analysis aims to know and discuss the framing structure made by media Kompas and Viva in reporting the employment of Chinese foreign workers in the KCJB project, which had made the community stormy because the Government chose to use foreign workers instead of local workers. The type of research used is qualitative research with Pan and Kosicki's framing analysis approach due to their explanation of framing, which is the process of making messages or information more prominent and making readers more focused on the message conveyed. The results of this study indicate that in terms of the syntactic structure, Kompas and Viva try to be neutral by using direct quotations in their titles and only conveying the facts. Thematically, Kompas and Viva provide good factual information because both media convey the existing facts as a unity without reducing or changing the facts obtained from the sources. Judging from the delivery of information, Kompas and Viva seem only to convey what it is without adding opinions or cutting facts. Rhetorically, both of them do not give emphasis and only convey facts obtained from the source. And even though they both lack the completeness of the 5W + 1H elements in some of their articles, they do not affect the core of the news delivered. Keywords: Framing, Highspeed Rail, Welder, Foreign Worker